Design and implementation of a cloud computing platform for electromagnetic modelling. (2015) - Caragnano, Giuseppe; Mossucca, Lorenzo; Francavilla, Matteo Alessandro; Ruiu, Pietro; Terzo, Olivier
Cloud computing has recently attracted attention in numerical simulation fields; its appeal is mainly due to the possibility of providing high computational resources at low cost. Computational electromagnetics (CEMs), aimed at numerically predicting the electromagnetic behaviour of arbitrary objects (e.g., aircrafts, satellites, ships, antennas, etc.), often requires computational resources unavailable on single workstations. This is where cloud computing comes into play, as a potential low cost solution for the EM analysis. For these reasons, the development of accurate and efficient EM models, together with an appropriate use of computational resources in cloud is a research topic with a strong industrial interest. In this work, the authors present the results of the cloud infrastructure for CEM problems developed within the project 'Cloud fast scalable EM modelling - CloudCEM'.